Workplace Empowerment, Job Satisfaction, and Teaching Performance of Public Senior High School Teachers’ in City Schools Division in the Province of Laguna - Mapacpac, Greg Jr.; Yango, Antonio (Technium Social Sciences Journal, 2023)
Teachers’ empowerment is one of the most effective ways to enhance teachers’ commitment (Muhammad & Hussain, 2020). They have a very high level of workplace empowerment along impact which shows that teachers believe that they affect and influence school life positively. The goal of this study was to explore the level of teachers’ workplace empowerment, job satisfaction, and teaching performance, probe the relationship between the teachers’ level of workplace empowerment and level of job satisfaction, workplace empowerment and teaching performance, and level of job satisfaction and teaching performance, and examined the predictive ability of the level of workplace empowerment, and job satisfaction, taken singly or in combination, of level of teaching performance of senior high school teachers’ in the City Schools Division in the Province of Laguna. The findings revealed that the teachers’ level of workplace empowerment was “highly empowered”, while the teachers’ level of job satisfaction was “very satisfactory”. On the other hand, the teachers’ level of teaching performance was “outstanding”. In addition, the teachers’ level of teaching performance was significant to meaning, benefits, and professional growth with a p-value of 0.023, 0.028, and 0.002, respectively. It was concluded in the study that teacher’s workplace empowerment only meaning was correlated to teachers’ level of teaching performance. While in terms of job satisfaction, benefits and professional growth was correlated to teachers’ level of teaching performance. It implied that these predictors were highly contributors to the teachers of teaching performance. This study is believed to be a beneficial reference in developing a more empowered workplace, highly pleased teaching forces with the finest teaching performances.